Engaging Populations With Long-Term Conditions: Insights From ExWell Community-Based Physical Activity Programmes in Ireland (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Long-term conditions (LTCs) impact quality of life. As life expectancy increases, ensuring individuals lead fulfilling lives whilst supporting sustainable healthcare systems is essential. Extensive evidence demonstrates exercise rehabilitation efficacy in LTC management. In Ireland, accessibility to community-based services for LTC management is growing. ExWell, a community-based physical activity (PA) programme for populations with LTC reaches 5,000 individuals weekly across 50 centres nationwide. Despite such extensive participation, participants’ demographic profiles remain unclear. This study aims to examine demographic characteristics of ExWell participants and identify potentially underserved populations.Methods: Data were collected at ExWell inductions, where participants, referred by healthcare professionals, engaged in exercise classes. Five hundred twenty-eight participants aged 22–93 years (mean age 70.5 ± 9.93 yrs.) were recruited. A 20-item questionnaire was distributed, capturing demographics, self-rated health (EQ-5D), mental wellbeing (WEMWBS, UCLA Loneliness Scale), and healthcare utilisation. Data were analysed using IBM SPSS version 29.0.1.0 (2023).Results: Two-thirds of participants were female (63.7%, n = 337). Participant ethnicity was 96.8% White. According to Ireland’s Central Statistics Office’s (CSO) 2024 census, 25% of the general population are aged 60–75 years, this aligns with 54.1% of ExWell’s study sample falling within this age bracket. Participants reported a diverse range of LTCs, with high prevalence of cardiovascular (74.7%) and musculoskeletal (66%), which corresponds with 2020 TILDA (The Irish Longitudinal Study on Ageing) data on disease prevalence in this cohort. Most (98.2%) of participants presented with multimorbidity, comparable with TILDA data stating over three-quarters of adults >58 years-old have ≥2 LTCs. Females reported significantly higher numbers of LTC than males (3.71 ± 1.9, 3.26 ± 1.7, p < 0.05). Males rated life satisfaction significantly higher than females (6.97 ± 2.4, 6.44 ± 2.5, p < 0.05). Spearman’s rank correlation showed a moderate negative correlation between number of LTCs and self-rated health (p = –.323, p < .001).Conclusion: Preliminary findings highlight that men, broader ethnic groups, and younger individuals with LTC may be under-represented. Demographic profiles of this sample align with corresponding CSO and TILDA data. Follow-up research will explore barriers potentially preventing underrepresented populations from engaging in ExWell. These findings may suggest the need to adapt strategies for promoting PA engagement amongst individuals with LTC, potentially enhancing programme sustainability. Support/Funding Source: SETU Co-Fund and Carlow Sports Partnership.